An Efficient Image De-Blurring Technique Using Point Spread Function in High Definition Medical Image - Mohammed Anwar; Abubakar Muhammad Ashir (Eurasian Journal of Science and Engineering, 2020)
Medical image-enhancing technology plays a significant role for processing and revealing discerning information from acquired images in many applications such as Magnetic Resonance Imaging (MRI) and Computed Tomography (CT) which are frequently used for diagnosis and treatments in medical imaging. The clarity of these images become of great importance considering the details required to render diagnosis. The effects associated with blurred images in such applications is very challenging. The blurring effect is largely unavoidable due to the errors associated with capturing devices and natural motion in the human body. In this research, a method is proposed utilizing image blending approach to significantly reduce the effects of blur from an image through motion adaptive Point Spread Function (PSF). The proposed Efficient Image De-Blurring methods (EIDB) is realized using PSFs. And then get deblurred quality images from image de-blending image set in the alpha plane.